Associations between socioeconomic factors, residence, physical activity, dietary trends and nutrition: Results from the 2019-2021 Icelandic National Dietary Survey - Margrét Jóhannsdóttir 1995- (2023)
Aims: To examine the associations between socioeconomic factors, residence, physical activity, dietary trends and nutrition. Method: This study used data from the 2019-2021 Icelandic National Dietary Survey, with participants aged 18-80 years. Data was collected using two 24-hour recalls, a food frequency questionnaire, and a background questionnaire. Binary logistic regression, the Mann-Whitney U-test, and the independent samples t-test were used for statistical analysis. Results: There were 822 participants, of whom 52 (6%) followed a low-carbohydrate diet and 28 (3%) reported practising intermittent fasting. Higher education was associated with more frequent consumption of fruit and vegetables, regular intake of vitamin D supplements, and less frequent consumption of sugar-sweetened beverages. Difficulty in making ends meet economically was associated with more frequent consumption of sugar-sweetened beverages (odds ratio (OR) 2.74, 95% confidence interval (CI): 1.18-6.33) as well as artificially sweetened beverages. Living in the Capital Area was associated with more frequent consumption of vegetables compared with living elsewhere in Iceland (OR 1.63, 95% CI: 1.22-2.18). Frequent physical activity was associated with more frequent consumption of fruit and vegetables as well as regular intake of vitamin D supplements. Those following a low-carbohydrate diet had lower intake of total carbohydrates, added sugars, and fibre, and higher intake of protein, total fat, and saturated fat than those without dietary restrictions (p<0.05). Those practising intermittent fasting also had lower total carbohydrate intake and higher protein intake (p<0.05). Conclusion: Those with higher education and who exercise frequently in their leisure time are more likely to follow dietary recommendations. Difficulty in making ends meet economically and area of residence can affect dietary choices. Those who followed a low-carbohydrate diet or practised intermittent fasting were less likely to consume macronutrients within ...